(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
Body temperature is maintained by effective thermoregulation, which depends on heat balance that includes heat production and heat loss. Skin moisture and water evaporation from the body play an important role in heat transfer, especially during exercising or in hot conditions. The regional skin evaporation can significantly affect the heat release of the each body part, the pattern of skin temperature distribution and the thermoregulation. Indeed, the distribution of sweat evaporation and skin temperature can also be applied as a means of managing the body thermoregulation. This study reviews the thermoregulation of human body, local skin evaporation and the skin temperature distribution. It also highlights the implication of local skin evaporation and skin temperature in the development of sportswear and the prevention of heat disorder in hot conditions.